Pelatihan Dan Pendampingan Pelabelan Keripik Pisang Untuk Membantu Produksi Umkm Di Kampung Asyaman Kabupaten Keerom - Nainggolan, Hotnida; Mini, Marthina; Manulang, Evanita V.; Rumabar, Anna Maria (Jurnal Ilmiah Wahana Pendidikan, 2023)
KAsyaman Village is one of the villages in Keerom district which has quite abundant agricultural products. Many plantations owned by the community are planted with banana trees. One form of processed banana plant is banana chips. So far, the people of Asyaman village process banana chips and sell them at kiosks or stalls without labels. Apart from that, the people of Asyaman village do not yet understand marketing through market places or online via social media. Based on the problems faced, this service approaches using qualitative methods, through interviews, observations and literature studies. The results obtained include making packaging labels and marketing training via social media. Through community service activities carried out with the aim of providing solutions to problems for the community in Asyaman village in particular and the entire community of Keerom district in general in order to increase knowledge and skills in managing existing agricultural products by utilizing technological advances. With assistance to MSME owners in Asyaman village, especially processing banana chips, they can make labels on their business products and also sell their products online through the market place.